2018
DOI: 10.4049/jimmunol.1701687
|View full text |Cite
|
Sign up to set email alerts
|

Brief Exposure of Skin to Near-Infrared Laser Modulates Mast Cell Function and Augments the Immune Response

Abstract: The treatment of skin with low-power continuous wave (CW) near-infrared (NIR) laser prior to vaccination is an emerging strategy to augment the immune response to intradermal vaccine, potentially substituting for chemical adjuvant, which has been linked to adverse effects of vaccines. This approach proved to be low-cost, simple, small, and readily translatable compared to the previously explored pulsed wave (PW) medical lasers. However, little is known on the mode of laser-tissue interaction eliciting the adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 107 publications
(177 reference statements)
4
41
0
Order By: Relevance
“…Kimizuka et al further revealed that continuous wave 1064 nm laser-induced generation of reactive oxygen species (ROS) in the exposed skin and transiently stimulated mast cells, leading to expression of a defined set of chemokines including CCL2 and CCL20 that ultimately induced CCL21 expression in the lymphatics without overt inflammation. 44 Our group further demonstrated that the immunostimulatory milieu established with the laser exposure induced migrational changes of skin-resident migratory CD103 + DCs, which played a pivotal role in augmentation of the adaptive immune response to the intradermal influenza vaccination (Figure 1). High-fluence low-power laser irradiation (HF-LPLI) has been consistently reported to target cytochrome c oxidase (COX) in electron transport chain (ETC) in mitochondria and induce generation of ROS.…”
Section: Non-pulsed Laser Adjuvantmentioning
confidence: 73%
See 3 more Smart Citations
“…Kimizuka et al further revealed that continuous wave 1064 nm laser-induced generation of reactive oxygen species (ROS) in the exposed skin and transiently stimulated mast cells, leading to expression of a defined set of chemokines including CCL2 and CCL20 that ultimately induced CCL21 expression in the lymphatics without overt inflammation. 44 Our group further demonstrated that the immunostimulatory milieu established with the laser exposure induced migrational changes of skin-resident migratory CD103 + DCs, which played a pivotal role in augmentation of the adaptive immune response to the intradermal influenza vaccination (Figure 1). High-fluence low-power laser irradiation (HF-LPLI) has been consistently reported to target cytochrome c oxidase (COX) in electron transport chain (ETC) in mitochondria and induce generation of ROS.…”
Section: Non-pulsed Laser Adjuvantmentioning
confidence: 73%
“…In this study, it has been suggested that thermal effect played a minimal role as the same dose of 1064 nm laser with a pulsed wave showed limited effects on the DC subsets and immune responses. Kimizuka et al further revealed that continuous wave 1064 nm laser‐induced generation of reactive oxygen species (ROS) in the exposed skin and transiently stimulated mast cells, leading to expression of a defined set of chemokines including CCL2 and CCL20 that ultimately induced CCL21 expression in the lymphatics without overt inflammation . Our group further demonstrated that the immunostimulatory milieu established with the laser exposure induced migrational changes of skin‐resident migratory CD103 + DCs, which played a pivotal role in augmentation of the adaptive immune response to the intradermal influenza vaccination (Figure ).…”
Section: Ultrashort Pulsed Laser Adjuvantmentioning
confidence: 84%
See 2 more Smart Citations
“…migDCs migrating into LNs from the peripheral tissues are defined by MHC class II hi CD11c int expression and further divided into Langerin − CD11b − , Langerin − CD11b + , Langerin + CD103 + CD11b − , and Langerin + CD103 − CD11b + Langerhans cells . cDCs are bone‐marrow derived, LN‐resident population and characterized by MHC‐II int CD11c hi expression containing CD11b + (CD8α − ) and CD103 + (CD8α + ) subsets . The number of cDCs and their subpopulations positive for the smaller model vaccines (OVA‐ZW and ONP1) was larger than those for the larger vaccine (ONP2) ( Figure A–C, cDC: OVA‐ZW versus ONP2, P = 0.0109; ONP1 versus ONP2, P = 0.0354; CD103 + cDC, OVA‐ZW versus ONP2, P = 0.0024; ONP1 versus ONP2, P = 0.0439), which reflects the fact that smaller vaccines directly enter the lymphatics and are taken up by cDCs 2c,7,19,26.…”
Section: Resultsmentioning
confidence: 99%